How to cope with (new) uncertainties: A bounded rationality approach - Werner Güth; Hartmut Kliemt (Kiel Institute for the World Economy (IfW), 2015)
A rigorous reconstruction of scenario-based real choice making reveals the incompleteness of decision-modeling and the practical prevalence of uncertainty. Theoretically complete models conceal it. As a remedy a scenario-based procedure of coping with uncertainty can prescribe how the boundedly rational decision-maker should proceed from her or his internal point of view. Though models of substantive rationality cannot serve as guidance for decision-making under uncertainty, we can improve prescriptions for coping with uncertainties in view of evidence of substantive success or failure. Decision theory should aim for a reflective equilibrium incorporating internalist-prescriptive and externalist-descriptive aspects to turn good into better practice.
Keywords: D80; D01; D03; D21; 330; uncertainty; procedural rationality; satisficing; risk-communication